Exploring the Positive Impacts of Technology-Enhanced Instruction on Student English Language Learning: A Systematic Literature Review - Tazkia, Zidni (Program Studi Magister Pendidikan Bahasa dan Sastra Indonesia, Program Pascasarjana, Universitas Pasundan Bandung, 2025)
This systematic literature review analyzes the use of technology in adopting teaching English language to secondary school learners in a critical way using 16 relevant peer-reviewed studies published between 2010 and 2024. By using the PRISMA framework, the authors describe how technological tools including Artificial Intelligence (AI), Virtual Reality (VR), multimedia applications, and game-based learning platforms contribute positively to the learning process of students as far as behavioral, cognitive and affective domains are concerned. Resources like the ChatGPT service, YouTube and Kahoot show the need for developing interactivity, increasing learning engagement and promoting learner independence through cooperation. Despite these advancements, the review also underscores persistent challenges, including infrastructural deficits, insufficient teacher training, and inequitable access to technology, particularly in under-resourced regions. These restrictions have become barriers to the integration and optimum application of technology in English language teaching (ELT). The synthesis ends by pointing out some of the shortcomings in extant research, especially the moderate emphasis placed on understanding how learner characteristics and socio-economic environments moderate the effects of technology-supported pedagogy. The overall conclusions are intended to inform instructional and policy decision-making for educators, policymakers, and researchers to improve technology-based instruction and foster inclusive and sustainable processes to support the teaching of English as a foreign language.